2008
DOI: 10.1111/j.1399-5618.2008.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Wisconsin Card Sorting Test performance in bipolar disorder: effects of mood state and early course

Abstract: Executive dysfunction may be a mediating vulnerability indicator of bipolar disorder that is strongly related to mood state, but only modestly related to chronicity of illness during the early disease course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 36 publications
2
31
0
1
Order By: Relevance
“…Meta-analysis also denoted that the euthymic bipolar patients have distinct impairments of executive function, verbal memory, psychomotor speed, and sustained attention [50]. Findings in the current study are consistent with previous studies in large, which showed significant poorer performance among majority of measures in neurocognitive tests of attention and executive function in patients with BP-I compared to healthy controls [51,52]. No differences were found between patients and controls in two measures of trail marking A, errors and illegal times.…”
Section: Discussionsupporting
confidence: 90%
“…Meta-analysis also denoted that the euthymic bipolar patients have distinct impairments of executive function, verbal memory, psychomotor speed, and sustained attention [50]. Findings in the current study are consistent with previous studies in large, which showed significant poorer performance among majority of measures in neurocognitive tests of attention and executive function in patients with BP-I compared to healthy controls [51,52]. No differences were found between patients and controls in two measures of trail marking A, errors and illegal times.…”
Section: Discussionsupporting
confidence: 90%
“…Many of the existing studies indicate disorders in executive functions measured with the WCST in this group of patients [7,12,16,24]. As far as patients in the depressive phase are concerned, the study by Martinez-Aran et al [7] shows that they made significantly more perseverative errors in the WCST than healthy persons, yet there were no differences in the number of properly completed categories between those groups.…”
Section: Discussionmentioning
confidence: 77%
“…According to other authors, the performance on the executive function measures was bimodal among euthymic BD patients (one subgroup with relatively normal and one subgroup with impaired executive functioning) (Altshuler et al 2004 ). Some studies report no difference in executive function between BD patients and controls (Paradiso et al 1997 ;de Almeida Rocca et al 2008 ;Fleck et al 2008 ;Olley et al 2005 ;Thompson et al 2007 ;Friedman et al 1977 ), while one study suggested that impairment is present only in the more severe and chronic cases (de Almeida Rocca et al 2008 ).…”
Section: Executive Functionmentioning
confidence: 97%